Identifikasi Lahan Pertanian Di Dataran Fluvial Wilayah Kabupaten Kulonprogo Dengan Menggunakan Aplikasi Sistem Informasi Geografi Dan Penginderaan Jauh - Wahyuningrum Rizka, Rizka; , Dr. Ir. Imam Hardjono, M.Si; , Ir. Taryono, M.Si (2015)
IDENTIFICATION OF AGRICULTURAL LAND IN PLAIN FLUVIAL KULON PROGO REGENCY APPLICATIONS USING GEOGRAPHIC INFORMATION SYSTEMS AND REMOTE SENSING Rizka Wahyuningrum1, Imam Hardjono2, Taryono3 1Student Faculty of Geography Muhammadiyah Surakarta University 2,LecturerFaculty of Geography Muhammadiyah Surakarta University Rizkawahyuningrum16@gmail.com E100140113 ABSTRACT Along with the rate of conversion of agricultural land to non-agricultural land, agricultural resources which need to be given priority is agricultural land. land conversion is irreversible (can not be returned) by processing agricultural land varies from time period to time, while the effort to cope with a decrease in productivity is constrained by the development budget, limited land resources and technological innovation. The purpose of this study were (1) the identification of agricultural land in the fluvial plains of Kulon Progo district (2) to analyze the distribution of agricultural land in the fluvial plains of Kulon Progo Regency. The method used is a visual interpretation of Landsat 8 for intercepting the data of physical parameters such as land use and land cover. This study reinforced with field surveys to obtain data as well as additional maps help landform, soil type, rainfall, slope and maps dry and wet-rice paddy. Next to overlay, then knowing the distribution of agricultural land in fluvial plains. Results of research in the form of a map distribution of agricultural land in fluvial plains. Based on the research that has been done can be some conclusions as follows: (1) The image landasat 8 are very supportive for the identification of agricultural land as it can record object kenampakkan well making it easier for the identification of agricultural land, this is indicated by the level of accuracy of 79.8 % (2) Identification of agricultural land in the fluvial plains of Kulon Progo district is dominated by irrigated rice field: rice 2x / year-over, which is located in the area Temon districts, Wates, Panjatan, and Nanggulan. Keywords: Landsat 8, Distribution of agricultural land, Fluvial Plains, Analysis